Diagnostic and therapeutic challenges of BRASH syndrome - Fateen Ata (12217764) (2021)
Rationale BRASH syndrome is a relatively unknown medical entity in which there is a combination of bradycardia, renal injury, hypoperfusion, and hyperkalemia. It is clinically essential to take these manifestations as a syndrome rather than isolated findings because they are interrelated and have synergistic effects. Bradycardia can result in hypoperfusion, which can cause renal injury. The resultant renal injury causes hyperkalemia (which can also be the initial trigger), which potentiates the bradycardia. Deteriorating patients with the syndrome usually do not respond to regular Advanced Cardiac Life Support resuscitation protocols. Treatment focused on the timely replacement of fluids and electrolytes gives better outcomes. It is vital to keep BRASH syndrome in diagnostic possibilities while seeing patients with refractory bradycardia, hyperkalemia, and renal injury, especially when other diagnoses are ruled out. Patient concerns In this report, we present a 64-years-old gentleman who came with generalized fatigue, non-bloody diarrhea, vomiting, and low oral intake for the past 5 days. Diagnoses The patient was diagnosed with BRASH syndrome. Interventions The patient received intravenous fluids, 2 doses of atropine 0.5 mg and received dextrose 50 percent with insulin regular 10 units, and salbutamol 5 mg for hyperkalemia. He was intubated due to a low Glasgow Coma Scale and received dialysis for resistant hyperkalemia. A transvenous pacemaker was inserted due to bradycardia. Outcomes The patient had 2 cardiac arrests and could not survive the second. Lessons BRASH is a life-threatening yet largely underdiagnosed condition. Physicians should keep a high index of suspicion for BRASH while seeing patients with resistant and self-potentiating bradycardia, hyperkalemia, and renal failure, as a timely diagnosis is crucial in the management. Variable clinical presentations and limited literature create a diagnostic challenge. Further studies are warranted to understand the pathophysiology and develop better and accurate management algorithms. Patients’ risk of developing BRASH syndrome should be considered while prescribing causative medications (Atrioventricular nodal blocking drugs such as beta-blockers) in hospitals and outpatient settings. Other Information Published in: Medicine: Case Reports and Study Protocols License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1097/md9.0000000000000018